Emotion regulation, depression and self-harming behaviours in people with borderline personality disorder: the moderating role of action vs. state orientation - Sybilla Blasczyk-Schiep; Paulina Jaworska-Andryszewska; Ewelina Rabska; Agnieszka Lason; Ewa Niezgoda; Karolina Fila-Witecka (Current Issues in Personality Psychology, 2016)
Background The aim of this research is to determine the level of emotion regulation, studied through the method of variable action orientation vs. state and its relationship with depressiveness and dimension of the reasons for living and self-harming behaviour of patients with borderline personality disorder.